A new deep-sea genus of nannastacidae (Crustacea, cumacea) from the lucky strike hydrothermal vent field (Azores triple junction, mid-atlantic ridge) - Corbera, Jordi (2008)
A new cumacean genus and species, Thalycrocuma sarradini gen. et sp. nov., belonging to the family Nannastacidae is described from several sites of the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge, 37N, 1700 m depth). The new genus differs from others in the family by males lacking exopods on the pereopods 3 and 4 and having an antenna with a five-articulate peduncle and a short flagellum. This is the first cumacean species that could be considered, at the moment, as endemic from hydrothermal vent areas. Data on the accompanying fauna including other cumacean species (Cyclaspis longicaudata, Bathycuma brevirostre, Procampylaspis sp. and Makrokylindrus sp.) and some ecological remarks are included. A key for the currently known genera of the family Nannastacidae is provided and the taxonomic position of some genera is discussed.